The Relativistic Jet Orientation and Host Galaxy of the Peculiar Blazar PKS 1413+135 - Readhead ACS (IOP PUBLISHING LTD, 2022)
PKS 1413+135 is one of the most peculiar blazars known. Its strange properties led to the hypothesis almost four decades ago that it is gravitationally lensed by a mass concentration associated with an intervening galaxy. It exhibits symmetric achromatic variability, a rare form of variability that has been attributed to gravitational milli-lensing. It has been classified as a BL Lac object, and is one of the rare objects in this class with a visible counterjet. BL Lac objects have jet axes aligned close to the line of sight. It has also been classified as a compact symmetric object-objects that have jet axes not aligned close to the line of sight. Intensive efforts to understand this blazar have hitherto failed to resolve even the questions of the orientation of the relativistic jet and the host galaxy. Answering these two questions is important because they challenge our understanding of jets in active galactic nuclei and the classification schemes we use to describe them. We show that the jet axis is aligned close to the line of sight and PKS 1413+135 is almost certainly not located in the apparent host galaxy, but is a background object in the redshift range 0.247 z z = 0.247 provides a natural host for the putative lens responsible for symmetric achromatic variability and is shown to be a Seyfert 2 galaxy. We also show that, as for the radio emission, a "multizone" model is needed to account for the high-energy emission.